AN EXAMINATION OF SOCIO-RELIGIOUS PRACTICES OF SUFI ADHERENTS IN BIDA, NIGER STATE - Abdulrahman Yahaya (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
Socio-religious concept is a term that was derived from a compound word of “social and religion” meaning different activities of people in communities which some historians suggested to be part and parcel of religions especially Islam. The paper seeks to encapsulate Bida in Nupe land, economic situation and locations where Nupe people are located in Nigeria, including their early religious worship such as Kuti (idol) which exist among people up to the time of introduction of Islam by some agents like Wangarawa Muslim scholars from Mali and Malam Muhammadu Bagana popularly known by Nupe people as “Manko” and others. The emergence of Sufism was assessed rightly from the time of Qadiriyyah Sufi practice and some scholars that were known with it like Sheikh Abdulrahman Muhammad bn Sharif and Sheikh Muhammad Wazir (1882-1945) called “Waziri Mamma” before the emergence of Tijjaniyyah Sufi order during the reign of 2nd Etsu Nupe Muhammadu Saba (1859-1873) known as “Ma’asaba” by Nupe people through a scholar Man-Haruna, alias “Man-yisa Naku” in Banwuya among people in Bida. The paper provides an overview of some socio-religious practices of Sufis in Bida, Niger State with the way and manner they are practice in accordance with the teachings of Islam. The paper examines the effects of training on adherents among Sufis in Bida, Niger State. In this paper, exploratory design method would be used for obtaining data from relevant areas of primary and secondary sources.